FACTORS AFFECTING DEBTOR COMPLIANCE IN CREDIT SETTLEMENT IN PT. MANDALA MULTIFINANCE Tbk, THE TILAMUTA BRANCH - Riska Koingo; Titin Dunggio; Sukrianto (Journal of Economic, Business, and Administration (JEBA), 2023)
The research objectives are: to determine the factors that affect debtor compliance in credit settlement at PT. Mandala Mtufinancial, Tbk Cab. Tilamuta. This type of research used in this research is a type of qualitative research with a descriptive approach. Researcher's descriptive approach wants to describe or describe the facts or circumstances or symptoms that appear in PT. Mandala Multifinance, Tbk Cab.Tilamuta. The results of this study are that natural factors that hinder debt repayment are crop failure for farmers and business instability by Civil Servants (PNS) because at this time they are still in the process of monitoring the Covid-19 pandemic. The consumer character that appears because the attitude and service of the company are not in accordance with the initial promise that the creditor has conveyed to the debtor. At maturity, the creditor provides a grace period of 3 days even up to 1 week when due, although the creditor has been given a grace period, unlike providing relief because the intervals of one day at maturity have been contacted directly by the company. The settlement taken by the company or the debtor in the process of handling credit is in the form ofRescheduling, Reconditioning and Restructuring.